Factors affecting dining satisfaction and acceptability of food item among athletes during a sporting event - Mohd Ali, Mohalijah; Boo, Huey Chern; Abdul Karim, Muhammad Shahrim; Abu Bakar, Ainul Zakiah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Athletes are a special group of consumers whose specific diet requirement is important during training and competition to ensure their success. As commercial foodservice establishments are increasing involved in providing foods to this group of consumers on one hand and the lack of research investigating the athletes' dining satisfaction, especially meeting their diet requirement on the other hand, this study was conducted to investigate the influence of nutritional factors in athletes' dining satisfaction and the acceptance of various foods provided in an international sporting event. Following a stratified random sampling, 700 athletes were selected from the entire population of 1330 participants. The final usable sample size was 450 (64.3% response rate). Regression analysis revealed that overall service, overall food quality, grooming of server, and nutritional information tag significantly influence the overall dining satisfaction among athletes. In addition, nutritional value, menu variety, fat content, freshness, and taste were found as the most important determinant in almost all food categories. It is intriguing that meeting diet requirement is not a significant factor but nutritional information tag is. Important implications were discussed. Nutrition education is recommended for foodservice operators especially when they are involved in providing food for sporting events. It is advisable that an appointed specialized sport dietitian or nutritionist to a sporting event works together with the foodservice operators to ensure that the menu meets the nutritional requirement of athletes.